2001, a space odyssey - Kubrick, Stanley; Clarke, Arthur Charles, 1917- (Santa Monica, CA : MGM Home Entertainment, 1998)
A science fiction film which moves from the pre-historic birth of intelligence toward the emergence of man as pure thought somewhere in the future.
Originally produced as a motion picture in 1968.
Includes interview with Arthur C. Clarke and original theatrical trailers for 2001 and 2010.
Director of photography, Geoffrey Unsworth ; film editor, Ray Lovejoy.
Keir Dullea, Gary Lockwood.
DVD player required.
Dialogue in English with optional French soundtrack, and optional subtitles in French and Spanish.
Keywords: Twenty-first century -- Drama; Computers -- Drama; Space vehicles -- Drama; Human-computer interaction -- Drama; HAL (Fictitious character) -- Drama; Science fiction films; Video recordings for the hearing impaired